The Impact of Including Moringa oleifera Leaves to Lower Potassium Dichromate Toxicity on Rabbit Reproductive Outcomes Under Heat Stress - Fayrouz khaled,; Osama Aldeeb,; Abdulsalam Abdulsalam, (AlQalam Journal of Medical and Applied Sciences, 2024)
Although chromium is a necessary element for healthy physiology, excessive amounts of it can be harmful to humans. Despite an increasing body of evidence about the effects of chromium exposure on human health, there is still a lack of agreement regarding semen quality. The incredibly lively and stimulating moringaoleifer (MO) is one of the first extensively dispersed species of the Moringaceae family. Due to its many health benefits, it has been highly respected since ancient times. Every portion of the tree has high alimentary properties, making it suitable for use in both commercial and nutritional contexts. This study's goal was to ascertain how feeding moringa oléifera leaves 'MO' to rabbits under heat stress could lessen the toxicity of potassium dichromate Cr'VI' and improve their ability to reproduce. The animals were divided into 4 groups: 400 mg 'MO'/kg bw, 5 mg Cr'VI'l/kg bw, 400 mg 'MO'/kg bw, and Cr'VI' (5 mg/kg bw) plus 'MO' (400 mg/kg bw). Results demonstrated that Cr'VI' treatment reduced (P<0.05) sperm motility index, sperm concentration, ejaculate volume, and semen beginning fructose content. There was a dose-dependent negative relationship between Cr'VI' and semen characteristics. Treatment with Cr'VI' led to a dose-dependent increase (P<0.05) in the number of aberrant and dead sperm. During treatment, treatment with, moringa oleifera 'MO' reduced the adverse effects of Cr'VI'. The outcomes showed that MO had a positive impact on mitigating the detrimental effects of Cr'VI' on male rabbit fertility and productivity. These results provide credence to the possibility of using moringa oleifera as a natural dietary supplement to improve reproductive health in stressed-out rabbits kept These findings support the use of moringa oleifera as a natural dietary supplement to enhance reproductive health in anxious rabbits housed in harsh conditions or near pollutants. هدفت هذه الدراسة إلى تقييم تأثير إضافة أوراق المورينجا إلى النظام الغذائي في تخفيف سمية كرومات البوتاسيوم على الأداء التناسلي للأرانب الذكور تحت ظروف الإجهاد الحراري. أظهرت النتائج أن علاج كرومات البوتاسيوم له تأثيرات ضارة على العديد من المعايير التناسلية، بما في ذلك حجم السائل المنوي، وتركيز الحيوانات المنوية وتركيز الفركتوز في السائل المنوي. كانت هذه التأثيرات السلبية تعتمد على الجرعة.ومع ذلك، أظهرت الأرانب التي تلقت أوراق المورينجا تحسناً ملحوظاً في هذه المعايير التناسلية مقارنةً بالأرانب التي تعرضت فقط لعلاج كرومات البوتاسيوم. يشير ذلك إلى أن أوراق المورينجا يمكن أن تكون لها دور وقائي بفضل محتواها الغني من مضادات الأكسدة والفيتامينات التي تعمل على تقليل الأضرار الناتجة عن الإجهاد التأكسدي الذي يسببه كرومات البوتاسيوم.كما أظهرت الدراسة أن الإجهاد الحراري يعزز من التأثيرات السلبية لعلاج كرومات البوتاسيوم على الصحة التناسلية، وأن إضافة أوراق المورينجا يمكن أن تخفف من هذه التأثيرات بشكل كبير.تشير هذه النتائج إلى أن أوراق المورينجا يمكن أن تكون مكملًا غذائيًا طبيعيًا مفيدًا لتحسين الصحة التناسلية للأرانب المعرضة للإجهاد البيئي والكيميائي، خاصةً في البيئات ذات درجات الحرارة المرتفعة